Antara Bom Batu, Batam dan Jakarta: Perdagangan Keramik Hias Di Jambi Tahun 1980-2020 - Dennys Pradita; Ayu Adha Pratiwi (UIN Sunan Gunung Djati Bandung, 2023)
This research aims to analize determine the ceramic trade in Jambi through the Batu Bom Port which then the Ceramic Trade began to occur in the Sitimang Market and the impact of the ceramic trading activities in the Sitimang Jambi Market. Some of the problems raised are the beginning of the formation of the ceramic market in Jambi and the ceramic trade in Jambi after the closure of the Batu Bom Port. This research uses historical research methods. The findings of this study were the emergence of the ceramic market in Sitimang begins with a port that carries various commodities. Ceramics is one of the commodities brought by the ship and the existence of ship loading and unloading needs causes the Batu Bom Port area to emerge markets for shipping needs or sell products from outside vessels. However the Batu Bom Port was finally moved which caused ceramic traders to look for other ceramic trading centers such as Jakarta and Batam.